Human Resource Management at Mie Gacoan Jatiasih - Muhammad Ramli; Lisa Sarinah; Rizki Nurul Nugraha (West Science Social and Humanities Studies, 2024)
This research entitled “Human Resource Management at Mie Gacoan Jatiasih” wants to know how the human resource management system in Mie Gacoan Jatiasih. The purpose of the research is to find out the human resource management system at Mie Gacoan Jatiasih. The research was conducted on Jl. Wibawa Mukti, RT03/RW08, Jatiasih, Bekasi, West Java, Indonesia. The research method used is qualitative, with a qualitative descriptive approach and SWOC analysis. Data collection through field observations, interviews with resource persons, and previous research for reference in this study. The result of the research is that the management of Human Resource Management at Mie Gacoan Jatiasih has not been optimal in its development. The company needs to conduct further supervision related to employee performance must be in accordance with Standard Operating Procedures, because according to the results of observations that the human resources of Mie Gacoan Jatiasih still have not reached the standards provided by the company, especially in terms of customer service which will affect customer satisfaction.